V. I. Lenin on democracy - Pateman, Joe (2021)
This thesis explores the meaning and significance of ‘democracy’ in the political thought of V. I. Lenin, the founder of the Communist Party of the Soviet Union and the leader of the world’s first socialist state. Lenin’s views on democracy have significantly influenced communist politics and Marxist democratic theory. As such, it is important to establish precisely what he said on the subject. This thesis contributes to the literature by offering a more focused, systematic and complete analysis of Lenin’s pronouncements on democracy. It provides a fresh reading of the voluminous source material, whilst engaging with what the secondary literature has said as well. This thesis argues that Lenin should be recognised as a democratic theorist. Besides being committed to Marxism and the emancipation of the working class, Lenin is also concerned with the nature and value of democracy, including the theoretical and practical debates surrounding these issues. Lenin’s views on democracy have been routinely misunderstood and caricatured. He offers a more coherent, sophisticated, complex, and original perspective than is typically thought. To begin with, Lenin provides an insightful interpretation of the concept of democracy itself. Lenin highlights its class essence. Democracy for him expresses the rule of a definite class. From this proposition Lenin derives several theses. First, democracy is a political means of class struggle, and it cannot resolve that struggle. Democracy, as a part of the political superstructure, is reflective of and determined by the economic base of society. Second, democracy for one class means dictatorship for another. These phenomena are in dialectical unity, not opposition. Third, democracy precludes freedom. It cannot ‘free’ everyone, precisely because it is a form of class rule. These claims express Lenin’s view that democracy is a paradoxical concept, one containing inherent contradictions. Lenin’s class-based perspective provides a unique lens through which to conceptualise democracy more critically. Lenin also offers a provocative critique of liberal democracy, or what he calls ‘bourgeois’ democracy. Lenin’s critique amounts to three core claims. First, liberal democracy leaves the economic sphere, a crucial zone of political power, in the hands of the unaccountable bourgeoisie. Second, democratic rights are restricted by private property ownership and are therefore used to cement bourgeois domination. Third, the liberal state privileges the power of a wealthy propertied oligarchic elite, whilst effectively barring the working class from politics. Lenin’s critique builds upon the ideas of Marx and Engels, though it is not a simple rehash. He provides an original examination of democracy under imperialism; and avoids some of the more controversial aspects of Marx and Engels’ critique, specifically their principled rejection of individual rights. Last but not least, Lenin offers a bold vision of socialist democracy, or what he calls ‘proletarian’ democracy. The distinctive feature of his conception is the leading role of the Communist Party, the chief organ of the working class. Socialist democracy provides a range of civil, political, economic, social and cultural freedoms. The masses participate in the daily administration of the state. Political organs operate in accordance with democratic centralism. Democracy extends into the economy, as the workers manage their enterprises in accordance with a state economic plan. Lenin’s vision features a tension between top-down control and bottom-up spontaneity. He inadequately addresses issues relevant to democratisation, such as the power and role of the Party, the protection of democratic rights, the balance between economic planning and workers’ management, the autonomy of social and state organisations, and the contradiction between centralism and democracy. Nevertheless, Lenin’s conception is flexible. It encourages a range of interpretations and applications.